Challenges and solutions in sexual health among women after treatment for malignant neoplasms of the female reproductive system - G. V. Dadalyan; A. A. Saakyan; S. D. Adamova; Kh. Kh. Alimkhanova; B. A. Aidaeva; N. M. Magomedova; A. R. Kabdegalieva; R. A. Besheeva; D. A. Osmanov; I. Z. Ersmurzaeva; I. A. Khalisov; S. U. Shafikova; et al. (Акушерство, гинекология и репродукция)
Sexual dysfunction is one of the most common and underestimated issues observed in women undergone treatment for malignant neoplasms of the female reproductive system. Here, we review current data on the impact of surgical treatment, radiation therapy, and chemotherapy on patients’ sexual health, including symptoms such as vaginal dryness, dyspareunia, decreased sexual desire, and dissatisfaction with intimate life. Special attention is paid to the importance of screening for sexual dysfunction at all stages – from diagnosis to long-term survival. We discuss modern approaches to managing sexual dysfunction, including hormonal and non-hormonal therapies, vaginal moisturizers and lubricants, use of vaginal dilators, pelvic floor physical therapy, psychosocial counseling, and local anesthetic application. The effectiveness of multidisciplinary programs implemented in specialized sexual health clinics is highlighted, along with the growing importance of telemedicine and online resources for patients living in areas with limited access to specialized care. The article also addresses sexual health inequity access to services among marginalized groups, including individuals with low socioeconomic status, residents of rural areas, and members of sexual and gender minority communities. The need to increase awareness among healthcare professionals, integrate sexual health screening into routine oncology practice, and develop individualized rehabilitation programs to improve the quality of women’s life after gynecologic cancer treatment is emphasized.